Carbon reactivity in biomass thermal breakdown. (1st November 2016) - Volpe, Roberto; Messineo, Antonio; Millan, Marcos
Highlights: Up to 500 °C, FC increases mainly due to volatilization of reactive elements. Above 500 °C, FC keeps on increasing mainly due to deactivation reactions in solids. Carbon reactivity in chars correlates with H lost during thermal breakdown. Abstract: The thermochemical behavior of dry grape residues was assessed during pyrolysis experiments in a horizontal batch reactor. Grape marc (a mix of 50% seeds and 50% skins w/w% db) was pyrolysed during slow heating experiments (50 °C min −1 ) in a quartz reactor to peak temperatures between 150 and 650 °C, under a continuous flow of nitrogen (1.5 L min −1 ). Solids recovered after treatments (chars) were then subject to thermo-gravimetric analysis (TGA) in order to assess the reactivity of the carbon contained in them. Results on chars showed a linear increase of fixed carbon (FC) with reaction peak temperature. Elemental analyses on chars showed a consistent linear increase of Carbon (C) and a linear decrease of Oxygen (O) with reaction peak temperature. On the contrary, the Hydrogen (H) content remained relatively constant to approximately 325 °C and then decreased steadily as the reaction temperature was raised further. The reactivity of C in solids was investigated by definition of an index ρ(C), which was shown to remain approximately constant up to 325 °C and then significantly decrease above that temperature. The decrease of C reactivity initially related to the release of the more reactive C within the volatiles and then (for higher reaction temperatures) was shown to be mainly related to deactivation reactions within the solids. A correlation was shown between C reactivity and the release of H from thermal breakdown. As long as H concentration in solids remains constant (for reaction peak temperatures up to 325 °C), C reactivity remains close to the value found for raw feedstock. Then, between 325 and 400 °C, H content in solids decreases by 1.5% (w/w daf) and C reactivity drastically drops by 50%. This trend continues up to the highest reaction peak temperature tested (650 °C), for which the H content in solids is approximately 2% (w/w daf) and C reactivity drops by 70%. Elaboration of results from previous experiments on different feedstocks (as better described in Section3 ) also confirm this finding. We speculate that when temperature is raised to 250–325 °C, lower energy bonds are broken first as oxygenated compounds are released leaving large radicals behind. Findings from earlier studies on coal suggest that these radicals may either bond to each other to form heavier compounds or are quenched by unpaired Hydrogens (H radicals) to release oils/tars. When temperature is raised above 325 °C, unpaired H begin to bond to each other to form H2, therefore larger radicals more significantly bond to each other to form heavier less reactive compounds on char. At temperatures above 500 °C, carbon in char becomes more stable mainly due to rearrangement and deactivation reactions in solids.